Tahap kepuasan penonton terhadap pawagam LFS Cinemas Summer Mall, Kota Samarahan, Sarawak - Roslinda, Binti Kamarulzaman (Universiti Malaysia Sarawak (UNIMAS), 2015)
Satisfaction evaluate research related to audience LFS Cinemas Summer Mall, Kota Samarahan to unravel how satisfied the audience in the cinema can give good feedback from the audience itself and efforts to attract more viewers to go watch at the cinema in a state requirement the audience itself and not because of coercion, whether local or foreign tourist audience. At the end of investigation, our expected to deliver a good performance in the cinema audience satisfaction with the addition of more and more viewers can help to improve the film industry in our country.